2020
DOI: 10.1101/2020.05.19.103804
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent CPEB prion-like domains reveal different assembly mechanisms for a generic amyloid-like fold

Abstract: Functional amyloids are present in a wide variety of organisms ranging from bacteria to humans. Experience-dependent aggregation of the cytoplasmic polyadenylation element-binding (CPEB) prion-like protein to a translationally active state has emerged as a plausible biochemical substrate of long-lasting memories. CPEB aggregation is driven by prion-like domains (PLD) that are highly divergent in sequence across species. Here, we describe the amyloid-like features of the neuronal Aplysia CPEB (ApCPEB) PLD in vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Whereas Aplysia and mammalian CPEB homologs share a similar domain organization with Drosophila Orb2, they lack the multiple His residues interspersed in their Q-rich segments (40,43,44) which are found in Orb2. This suggests that the pHregulated nature of Orb2 amyloid formation and dissociation may be substituted by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Aplysia and mammalian CPEB homologs share a similar domain organization with Drosophila Orb2, they lack the multiple His residues interspersed in their Q-rich segments (40,43,44) which are found in Orb2. This suggests that the pHregulated nature of Orb2 amyloid formation and dissociation may be substituted by other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting helical conformations may drive association processes such as the formation of coiled-coils, as seen for other proteins which undergo liquid-liquid phase separation via intermolecular helical associations (Conicella et al, 2016). Q-rich coiled-coils and higher oligomeric species have been proposed as intermediates in amyloidogenesis of Aplysia and mammalian CPEBs (Fiumara et al, 2010;Pelassa et al, 2014;Hervás et al, 2020b;Ramírez de Mingo, et al, 2020a), which are probably heterogeneous as strongly suggested by kinetic modeling (Vitalis and Pappu, 2011). A hypothetical working model which incorporates these ideas is shown in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothetical working model which incorporates these ideas is shown in Figure 5. Whereas Aplysia and mammalian CPEB homologs share a similar domain organization with Drosophila Orb2, they lack the multiple His residues interspersed in their Q-rich segments (Hervás et al, 2020b;Ramírez de Mingo, et al, 2020a) which are found in Orb2. This suggests that the pH-regulated nature of Orb2 amyloid formation and dissociation may be substituted by other mechanisms in higher organisms.…”
Section: Discussionmentioning
confidence: 99%
“…The polyQ binding peptide 1 (QBP1) has been previously shown to block the amyloid formation of several pathological amyloid-forming proteins, such as expanded polyQ tracts 40,41 and a TDP-43 Q/N-rich segment 42 , as well as Q/N-rich functional amyloids, such as Sup35 41 and hCPEB3 homologs from Aplysia (ApCPEB) 16 and Drosophila melanogaster (Orb2) 13 .…”
Section: Hcpeb3 Idr Organization: Structural Elements With Different mentioning
confidence: 99%
“…Moreover, the conformational trends within the PLD that precedes amyloid formation appears to be different among species. Thus, while the ApCPEB PLD forms α-helical coiled-coils in vitro and assembles into multimers to enhance amyloid aggregation [14][15][16] , the recombinant Orb2 PLD remains as a random coil conformation, which is able to oligomerize and form amyloid structures whose β-sheet core seems not to include the Q-rich domain 17 . By contrast, recent cryo-EM data revealed that Drosophila Orb2 from adult heads forms a threefold-symmetric hydrophilic amyloid core based on the Q-rich stretch 18 .…”
Section: Introductionmentioning
confidence: 99%